Características al sacrificio de canales de “cabrito transmontano” - Teixeira, Alfredo (2011)
The aim of this paper is to contribute to a better understanding of the butcher characteristics of the type of animal commercialized. This study used the database of the National Association of Raza Serrana Caprinicultores (ANCRAS) between 1998 and 2009, for live weight, carcass weight and killing-out percentage. The main selling season of kids is for the months of February to May to coincide with Carnival and Easter holidays. Regarding the kids consumer destination it confirms that the restaurants are the highest consumers. Data suggested a greater live weight of slaughtered between May and August compared to the months from October to January (10.1 vs 8.4 kg, respect) to the corresponding carcass weights of 5.6 and 4,7 kg. Carcasses preferred by restaurants are the heavier ones